The Effect of Using Different Geometric Shapes and Different Colors on the Development of Basic Football Skills - Younus, Ali Qutaiba; Rashid, Nawfel F. (Indonesian Journal of Physical Education and Sport Science, 2024)
The research aims to reveal the impact of proposed educational programs using different geometric shapes and various colors in the development of the art of skill performance for a number of basic football skills among fifth grade middle school students, experimental approach was used. The research community was represented by the fifth grade of middle school which numbered (133) students. The sample consisted of three divisions (a, c, d), they were deliberately selected, to match and approximate the hours of daily lessons, and thus the number of the sample for the three divisions reached (99) students, and a number of members of the sample were excluded, thus reaching the final sample number (42) students divided into (3) experimental groups by (14) students for each experimental group, and with a percentage of (31,587%) of the original community, The proposed educational programs were distributed to the groups by lottery, and the implementation of the educational programs took six weeks, distributed by two educational units per week for each group and the time of the educational unit was (45) minutes, and in light of the results of the research, the researchers concluded that the three educational programs have a positive impact on the development of the art of performing the basic skills selected in football, and the second experimental group, which was used (geometric shapes with cold colors), the researchers recommended emphasizing the use of geometric shapes with cold colors in the design of skill exercises used in the applied part of the lesson.